2017
DOI: 10.1111/jcap.12180
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors leading to increased rehospitalization rates among adolescents admitted to an acute care child and adolescent psychiatric hospital

Abstract: Adolescent clients who are admitted to an acute psychiatric hospital with a history of self-harming behavior and extended length of stay need to be identified and individualized treatment plans implemented for preventing repeat hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 9 publications
(29 reference statements)
1
25
1
1
Order By: Relevance
“…Although few have reported on changes in LOS for pediatric mental health conditions subsequent to the ACA, 22 it has been observed that psychiatric LOS has decreased over time despite increased rates of serious illness and self-harm. 12 Given that illness severity does not seem to drive LOS and that others have found that having a managed care payer 10 was a predictor of shorter LOS, it seems plausible that administrative and insurance factors have always had a disproportionately large influence on LOS for mental health indications.…”
Section: Discussionmentioning
confidence: 99%
“…Although few have reported on changes in LOS for pediatric mental health conditions subsequent to the ACA, 22 it has been observed that psychiatric LOS has decreased over time despite increased rates of serious illness and self-harm. 12 Given that illness severity does not seem to drive LOS and that others have found that having a managed care payer 10 was a predictor of shorter LOS, it seems plausible that administrative and insurance factors have always had a disproportionately large influence on LOS for mental health indications.…”
Section: Discussionmentioning
confidence: 99%
“…Although 20 family-related risk predictors were identified across all studies, only three predictors (primary caregiver, family psychiatric history, and history of child abuse or neglect) were measured in three or more studies and thus combinable via meta-analysis (Figure 1). Youths whose primary caregiver was a parent were at lower risk of readmission, compared with those with a nonparent caretaker (6,14,19), and this relationship approached significance (OR pooled =0.63, 95% confidence interval [CI]=0.38-1.04). Heterogeneity was very low (I 2 =0.0%).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 97%
“…Between 2005 and 2014, pediatric hospitalizations in U.S. children's hospitals rose five times more among children with a psychiatric diagnosis than among children without a psychiatric diagnosis (2). Recent studies suggest that one in four youths is readmitted to a psychiatric hospital within 1 year of discharge (3)(4)(5)(6), with most readmissions occurring within 3 months (7). Repeat hospitalizations disrupt social support and school performance and result in greater stigmatization for youths and their families (8,9).…”
mentioning
confidence: 99%
See 2 more Smart Citations